2002
DOI: 10.1289/ehp.02110613
|View full text |Cite
|
Sign up to set email alerts
|

A child with chronic manganese exposure from drinking water.

Abstract: The patient's family bought a home in a suburb, but the proximity of the house to wetlands and its distance from the town water main prohibited connecting the house to town water. The family had a well drilled and they drank the well water for 5 years, despite the fact that the water was turbid, had a metallic taste, and left an orange-brown residue on clothes, dishes, and appliances. When the water was tested after 5 years of residential use, the manganese concentration was elevated (1.21 ppm; U.S. Environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 19 publications
5
95
1
Order By: Relevance
“…Mn concentrations in the range of 0.24-0.35 mg/L can lead to memory lapses in children. Similar findings have also reported decreased concentration and attentiveness in classes by children who drink water with a high Mn concentration [41,42]. Neurotoxicity has been implicated for adults over 50 years who drink Mn-rich water [43].…”
Section: Trace Metals Concentration Of Mvudi River Watersupporting
confidence: 61%
“…Mn concentrations in the range of 0.24-0.35 mg/L can lead to memory lapses in children. Similar findings have also reported decreased concentration and attentiveness in classes by children who drink water with a high Mn concentration [41,42]. Neurotoxicity has been implicated for adults over 50 years who drink Mn-rich water [43].…”
Section: Trace Metals Concentration Of Mvudi River Watersupporting
confidence: 61%
“…In Chinese children, exposure to elevated manganese concentrations in drinking water was associated with lower scores on tests of short-term memory, manual dexterity, and visualperceptual speed (65). We recently reported a child with manganism (blood Mn 3.8 μg/dL) from a private well water source with normal full scale IQ but deficits in verbal, visual and general memory indices (66). Using the McCarthy General Cognitive Index test at age 5 years, Takser et al (67) reported deficits in memory, attention and psychomotor indices associated with elevated umbilical cord Mn levels.…”
Section: Neurotoxicity Of Manganesementioning
confidence: 99%
“…Effects of Mn 2+ on working memory points to deficits in frontal cortex function, a brain region known to be involved in psychiatric illnesses such as schizophrenia (Abi-Dargham et al, 2002;Goldman-Rakic, 1999). Other reports also indicate effects of Mn 2+ exposure on the intellectual performance of children (Wasserman et al, 2006;Woolf et al, 2002).…”
Section: Introductionmentioning
confidence: 95%